Alexander’s i work on the Foundation Act for Dorpat University: a page from the history of liberal reforms in Russia at the beginning of the 19th century - Andrei Andreev; Yulia Gracheva (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article examines the process of discussion and approval of the Foundation Act of the Dorpat University, which formalized in Russian legislation the basic principles of university jurisdiction, which later became part of all university bills of the early 19th century. The initiator of the appearance of the Foundation Act was the professor and first rector of the University of Dorpat G. F. Parrot, who sought to include this higher educational institution in the all-imperial system of managing educational institutions. However, it was impossible to overcome the resistance of most of the leaders of the newly created Ministry of Public Education, who did not want the appearance of the medieval principle of autonomy in the university bill, without the active intervention of Emperor Alexander I. The monarch participated in the consideration of comments and amendments to the text at least seven times. It should be especially noted that the approval of the Foundation Act of the University of Dorpat became one of the few reforms of the beginning of the reign that were fully completed. The article uses Parrot's memoirs, his extensive correspondence with the emperor, as well as documents from Parrot's archive, currently stored in the Russian State Historical Archive. The researchers determined the circle of persons who were directly involved in editing the preliminary versions of the text of the Act. The authors come to the conclusion that Emperor Alexander I showed undoubted interest and personal perseverance in the work on the Foundation Act, involving in this work both figures of educational reforms, such as Minister P. V. Zavadovsky, M. N. Muravyov, S. O. Pototsky, and the circle of closest friends, primarily N. N. Novosiltsev and P. A. Stroganov.